1995
DOI: 10.1002/jlcr.2580361008
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [2‐{(4‐chlorophenyl) (4‐[125I]iodophenyl)} methoxyethyl]‐1‐piperidine‐3‐carboxylic acid, [125I]CIPCA: A potential radiotracer for GABA uptake sites

Abstract: SUMMARYThe synthesis of racemic [2-{(4-Chlorophenyl)(4-iodophenyl)) methoxyethyl]-l-piperidine-3-carboxylic acid, (CIPCA) and its radioiodinated analog [125I]CIPCA is described. CIPCA was synthesized from 4-iodobenzoyl chloride in five steps in 16% overall yield. Ammonium sulfate catalyzed solid-state isotopic exchange of CIPCA with Na125I provided [1251]CIPCA in 34% isolated radiochemical yield at a specific activity of 118 Ci/mmol. [125I]CIPCA demonstrated moderate brain extraction and good in vivo radiostab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Ethyl (2-hydroxyethyl)piperidine-3-carboxylate (6) was reacted with (12) in THF. The acetyl group was removed with sodium methanolate in methanol to yield (14). Finally, the hydroxy moiety was tosylated with tosyl chloride to yield compound (15) in an overall yield of 2.6% (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl (2-hydroxyethyl)piperidine-3-carboxylate (6) was reacted with (12) in THF. The acetyl group was removed with sodium methanolate in methanol to yield (14). Finally, the hydroxy moiety was tosylated with tosyl chloride to yield compound (15) in an overall yield of 2.6% (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The organic layer was dried over sodium sulphate, filtered, concentrated in vacuum and purified via flash-chromatography (ethylacetate/n-hexane/triethylamine, 1:1:0.1%) to yield the product (13) as a yellow oil (0.55 g, 0.88 mmol, 22% Ethyl(2-((4-(2-hydroxyethoxy)phenyl)bis(4-methoxyphenyl)methoxy)-ethyl)piperidine-3-carboxylate (14) 2-(4-(Bis(4-methoxyphenyl)(2-(3-(ethoxycarbonyl)piperidyl)ethoxy)methyl)-phenoxy)ethyl acetate (13) (0.4 g, 0.64 mmol) was dissolved in methanol and the pH value was adjusted to 8.5 with a 5% sodium methanolate solution in methanol (indicator: wet pH paper). This mixture was stirred overnight, water was added slowly, the precipitating solid was filtered off and dried in vacuum to yield ethyl (2-((4-(2-hydroxyethoxy)phenyl)bis(4-methoxyphenyl)methoxy)ethyl)piperidine-3-carboxylate (14) as a yellow solid (0.28 g, 0.5 mmol, 78%).…”
Section: -(4-(bis(4-methoxyphenyl)hydroxymethyl)phenoxy)ethan-1-ol (11)mentioning
confidence: 99%
“…Furthermore, 125 I-labelled CIPCA [ 125 I]33 has been synthesized by Van Dort et al . (Scheme 3 A) [ 72 ]. In their approach, CIPCA 33 was obtained from 4-iodobenzoyl chloride ( 32 ) in six steps.…”
Section: Lipophilic Gaba Analogues As Inhibitors and Radioligandsmentioning
confidence: 99%
“…Imaging studies in mice showed a low brain uptake of the radioligand (i.e. 0.82% of the injected dose) [ 72 ]. Thyroid radioactivity concentrations showed < 1% in vivo deiodination, ruling out this option as cause for the low brain uptake.…”
Section: Lipophilic Gaba Analogues As Inhibitors and Radioligandsmentioning
confidence: 99%
“…systems [107]. GABA uptake inhibitors may be useful tools for in vivo studies of central GABA neurotransmission in animals and man using positron emission tomography (PET) techniques.…”
Section: Behavioural and Clinical Pharmacologymentioning
confidence: 99%